(untitled) (Research, Society and Development, 2020)
Leptospirosis is an infectious and contagious bacterial disease that affects domestic and wild animals, in addition to being an important zoonosis. In dogs, it constitutes a serious public health problem, as they can be asymptomatic carriers, acting as reservoirs and, for this reason, animals present in Animal Protection Organizations can be reinserted in the community with intermittent elimination of the pathogen, which can cause contamination of other animals and man himself. The present study aimed to investigate the frequency of leptospirosis in dogs present in Animal Protection Organizations in the municipality of Caicó, state of Rio Grande do Norte, Brazil. The experiment was carried out from August to November 2017, when 35 blood samples were collected. The diagnosis of leptospirosis was determined by the Microscopic Soroagglutination Test (MAT) technique, using a collection of 24 serological variants. For the characterization of the most frequent serogroups, antibody titration was performed subsequently. The frequency found was 8.57% for the Pomona serogroup, the only one registered in the study and which has pigs as important reservoirs. It becomes necessary to avoid the contact of dogs with pigs and to implement the elaboration of disease control programs with actions directed to the use of vaccines for stray dogs and environmental sanitation, with the purpose of preventing the transmission of the disease to humans and others animals.